PENDIDIKAN MASYARAKAT BENTENG ALLA DI TENGAH PERGOLAKAN DI/ TII (1950-1961) - Abd Rahman; Abdurakhman Abdurakhman (Handep: Jurnal Sejarah dan Budaya, 2023)
This paper aims to analyze the efforts of Darul Islam/Tentara Islam Indonesia (DI/ TII) in realizing the formation of the Indonesian Islamic State amid the Indonesian National Army’s operations through educational aspects. This paper questions how the development of education provided by DI/TII to the people in its territory or conflict situation. The discussion is studied using historical methods with oral sources within the concepts of education and conflict. The conflict has always been synonymous with disruption and destruction of education; however, this historical study shows that education was intensified in conflict areas and used as a propaganda medium for DI/TII. This article presents the different conditions of education in areas controlled by the TNI and those controlled by DI/ TII. The results show that education for the people of Benteng Alla is still running despite being in a conflict situation between DI/TII and TNI. However, the education provided was built on the basis of DI/TII’s interest to establish an Islamic State so that it was not under state supervision.